Annie Oakley, Gender, and Guns: The "Champion Rifle Shot" and Gender Performance, 1860-1926 - Sarah Cansler (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2014)
Sharpshooter Annie Oakley’s enormous popularity provides a means of understanding how the public, through the viewpoints of reporters and commentators, discussed and understood the connection between gender and celebrity at the end of the nineteenth and beginning of the twentieth centuries. As a famous woman in an era rife with discussions about women’s rights and roles in society, Oakley’s popularity was inextricably related to ideas about gender. Oakley uniquely combined her talent at shooting, which many still viewed as a “man’s” sport, with her embodiment of appropriate feminine attributes like her clothing or mannerisms. Oakley’s performance of gender in the public sphere created her identity based on both her talent and on her femininity. She reveals ways in which she, as a famous woman, pushed the boundaries of expected gender roles and discourses in the late nineteenth and early twentieth centuries, and how reporters and audiences made sense of such a complex, multi-faceted, and public gender performance.